2018
DOI: 10.3389/fimmu.2018.00782
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Severe Combined Immunodeficiency Disease in Saudi Arabia Detected Through Combined T Cell Receptor Excision Circle and Next Generation Sequencing of Newborn Dried Blood Spots

Abstract: Severe combined immunodeficiency disease (SCID) is the most severe form of primary immunodeficiency disorders (PID). T-cell receptor excision circle (TREC) copy number analysis is an efficient tool for population-based newborn screening (NBS) for SCID and other T cell lymphopenias. We sought to assess the incidence of SCID among Saudi newborn population and examine the feasibility of using targeted next generation sequencing PID gene panel (T-NGS PID) on DNA isolated from dried blood spots (DBSs) in routine NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 45 publications
2
54
1
3
Order By: Relevance
“…This methodology could also be implemented in other Canadian provinces where these 2 founder mutations are also present in their Mennonite [14] and Indigenous communities [15] or can be adapted to other populations with their own specific founder mutations when there are false negative results with TRECS alone. Our approach is also conceptually similar to that described recently by Al-Mousa et al [7] using a Targeted-NGS [T-NGS] Primary Immunodeficiency panel in their Saudi population with a very high frequency of SCID. However, their approach is different from ours as T-NGS is a second tier mutation screening tool on DBS from Saudi newborns ascertained by low TREC assays.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This methodology could also be implemented in other Canadian provinces where these 2 founder mutations are also present in their Mennonite [14] and Indigenous communities [15] or can be adapted to other populations with their own specific founder mutations when there are false negative results with TRECS alone. Our approach is also conceptually similar to that described recently by Al-Mousa et al [7] using a Targeted-NGS [T-NGS] Primary Immunodeficiency panel in their Saudi population with a very high frequency of SCID. However, their approach is different from ours as T-NGS is a second tier mutation screening tool on DBS from Saudi newborns ascertained by low TREC assays.…”
Section: Discussionmentioning
confidence: 83%
“…Since then several countries including Israel [4], Taiwan [5] and one Canadian province of Ontario [6] have introduced newborn screening for SCID. Many others are conducting pilot projects or have proposals being considered [7][8][9][10]. The most widely used newborn screening test for SCID is the quantification of T-cell receptor excision circles (TREC) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal drug history is important since maternal intake of azathioprine was associated with low KREC level in offspring (24,25). In addition, ethnic differences in cutoff levels of TRECs and KRECs exist and remain to be studied on a larger scale [ (20,23,(26)(27)(28)(29)(30); Figure 1].…”
Section: Newborn Screening (Nbs) For Pidsmentioning
confidence: 99%
“…The mean age of diagnosis is 2 years in the MENA region (32). A pilot study on NBS using TRECs and KRECs in Saudi Arabia showed an increase in the number of patients diagnosed to have SCID reaching an incidence of 1 in 2,906 live births (29), which is a much higher incidence than in California (1/65,000) live birth (41). This highlights the importance of implementing NBS for the early detection of SCID in MENA region countries.…”
Section: Mena Region and The Challenges Aheadmentioning
confidence: 99%
“…Genomic DNA was extracted from whole blood using EZ1 DNA Blood 200-μL Kit (Qiagen). Targeted NGS was performed using a primary immunodeficiency gene panel 4 and Ion Torrent PGM sequencer (ThermoFisher) with an average coverage of 130X.…”
Section: Genetic Screening Of Primary Immunodeficiency Gene Defectsmentioning
confidence: 99%